Genetic prognostic markers in colorectal cancer. - Houlston, R; Tomlinson, I (1997)
The contribution of molecular genetics to colorectal cancer has been restricted largely to relatively rare inherited tumours and to the detection of germline mutations predisposing to these cancers. However, much is now also known about somatic events leading to colorectal cancer. A number of studies has been undertaken examining possible relations between genetic features and prognostic indices. While many of these studies are small and inconclusive, it is clear that a number of different pathways exist for the development of this cancer and some molecular characteristics correlate with clinicopathological features. With the advent of methods for the rapid genotyping of large numbers of colorectal cancers, it should be possible to evaluate fully the clinical usefulness of colorectal cancer genotypes through multivariate analyses.